2015
DOI: 10.1021/acs.jpclett.5b02186
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-Directed Control of Electronic Coupling for Singlet Fission in Covalent Bis–Acene Dimers

Abstract: While singlet fission (SF) has developed in recent years within material settings, much less is known about its control in covalent dimers. Such platforms are of fundamental importance and may also find practical use in next-generation dye-sensitized solar cell applications or for seeding SF at interfaces following exciton transport. Here, facile theoretical tools based on Boys localization methods are used to predict diabatic coupling for SF via determination of one-electron orbital coupling matrix elements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 53 publications
(139 reference statements)
2
56
0
Order By: Relevance
“…BT1‐ trans and BT1‐ cis are two such structures. In the third paper of this series, Damrauer and Snyder evaluated the effective eg ( ge )– tt couplings to be 1.1 and 2.0 meV for BT1‐ trans and ‐ cis , respectively. Despite the small magnitudes of all transfer integrals in BT‐1‐ trans , the constructive interference between the two CT branches gives an effective coupling comparable to that of BT1‐ cis .…”
Section: Exploration For Singlet Fission Mechanisms Through Electronimentioning
confidence: 99%
“…BT1‐ trans and BT1‐ cis are two such structures. In the third paper of this series, Damrauer and Snyder evaluated the effective eg ( ge )– tt couplings to be 1.1 and 2.0 meV for BT1‐ trans and ‐ cis , respectively. Despite the small magnitudes of all transfer integrals in BT‐1‐ trans , the constructive interference between the two CT branches gives an effective coupling comparable to that of BT1‐ cis .…”
Section: Exploration For Singlet Fission Mechanisms Through Electronimentioning
confidence: 99%
“…One obstacle for the application of the SF phenomenon in photovoltaics is that only a small number of molecules meet the two criteria: e.g., tetracene, 7 pentacene, 8-10 some of their derivatives, [11][12][13][14][15][16][17][18][19][20][21] perylenediimide, [22][23][24] and some polyenes. [25][26][27] Especially, research of SF is "overwhelmingly limited" to tetracene and pentacene.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that through artificial design strategies such as changing the symmetry of covalent dimer, breaking local crystal structures, controlling side chains or elements, one can effectively tune the couplings Vfalse˜1 and Vfalse˜2. The consequence of J‐ and H‐aggregates in aggregate spectra can be further borrowed to guide the tuning of Vfalse˜1 and Vfalse˜2.…”
Section: Methodsmentioning
confidence: 99%
“…Much attention has been given to the SF process recently for the potential of overcoming the Shockley–Queisser limit in single‐junction photovoltaic devices . Several works have found that the quantum interference between different pathways of the SF process, such as the direct and indirect CT‐mediated pathways, can have strong impact on SF rates . Interestingly, there is an analogous process in aggregate spectra, where a simple dimer model are denoted as H (J)‐aggregates when the direction of transition dipole moments of monomer are perpendicular (parallel) to the line connecting the the centers of monomer, with the higher (lower) excitonic states optically bright as revealed in the molecular spectra.…”
Section: Methodsmentioning
confidence: 99%